ISLAMIC ENTREPREUNERSHIP - Ruslan Husein (Jurnal Asy-Syukriyyah, 2015)
"Islamic entrepreneurship dictates that the individual must first be a religious person, then a practitioner (religious person who also practice what he learn). The benevolent person (insan berihsan) submits only to the Almighty. Through his/her vocation the person is expected to perform his/her duties as an ibadah and entrusted with the role of a responsible leader (khalifah)"